2017
DOI: 10.1101/221267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GDF15 Concentrations in Maternal Serum Associated with Vomiting in Pregnancy: the Cambridge Baby Growth Study

Abstract: Nausea and vomiting in pregnancy (NVP) affects 70-90% of all pregnant women but its pathogenesis is unknown. Growth and Differentiation Factor 15 (GDF15), secreted from the trophoblast and decidual stromal cells, is present at high levels in the blood of pregnant women. The receptor for GDF15 has recently been identified and is specifically expressed in the hindbrain where it transmits aversive signals including nausea and conditioned taste aversion. We explored the relationship between GDF15 concentrations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Even if this results (as it not infrequently does in humans) in a severe suppression of food intake in early pregnancy, the permissive leptin signal has already ensured there should be enough stored energy to maintain the growing fetus during the risky early stages of pregnancy. In support of this hypothesis, we have recently found that maternal GDF15 levels are significantly associated with pregnancy-related vomiting in humans (Petry et al, 2017).…”
Section: Figure 1 Gdf15 As An Endocrine Arm Of the Integrated Stress Responsementioning
confidence: 52%
“…Even if this results (as it not infrequently does in humans) in a severe suppression of food intake in early pregnancy, the permissive leptin signal has already ensured there should be enough stored energy to maintain the growing fetus during the risky early stages of pregnancy. In support of this hypothesis, we have recently found that maternal GDF15 levels are significantly associated with pregnancy-related vomiting in humans (Petry et al, 2017).…”
Section: Figure 1 Gdf15 As An Endocrine Arm Of the Integrated Stress Responsementioning
confidence: 52%
“…Hence, the organoids also mimic the villous placenta metabolically as well as endocrinologically. Peptides that induce physiological and metabolic adaptations during pregnancy, including hCG, KISS1 and CSH1 are all abundant as well as GDF15, implicated in hyperemesis gravidarum 16 . GDF15 and hCG are detected by ELISA, showing that full-length and appropriately folded hormones are secreted by trophoblast organoids (Fig.…”
mentioning
confidence: 99%
“…A genome wide association study found that genetic variants of the growth and differentiation factor 15 protein (GDF15) and insulin like growth factor binding protein 7 (IGFBP7) genes were strongly associated with NVP and HG 10. In another study, women with severe NVP symptoms who were taking anti-emetic medications in the second trimester had higher serum concentrations of GDF15 11. GDF15 is a hormone known to affect appetite, and is highly expressed in placental trophoblasts and decidual stromal cells.…”
Section: What Causes It?mentioning
confidence: 99%